1999
DOI: 10.1016/s0895-7061(99)00004-7
|View full text |Cite
|
Sign up to set email alerts
|

The Gly460Trp variant of α-adducin is not associated with hypertension in white anglo-Australians

Abstract: A Gly460Trp variant of the cytoskeletal protein ␣-adducin has recently been implicated in the etiology of essential hypertension (HT) in a study involving southern European whites. We attempted to replicate this finding in a well-characterized, extensively studied group of 112 white Australians with essential HT, with strong family history (two HT parents), early-onset, moderate to severe disease, and of British extraction. Controls were 196 normotensive (NT) white subjects whose parents were both NT older tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 30 publications
3
11
2
Order By: Relevance
“…In 10 populations, a positive association was found (10,13,32,42,80,116,119,124,156), whereas in two populations, a positive association was found only in women (128) or young subjects (132). In 13 populations, no association was present (2,3,38,70,74,79,84,88,100,116,119,124,151). In three studies (116,119,124), both positive and negative associations are observed in different populations.…”
Section: Studies In Humansmentioning
confidence: 89%
“…In 10 populations, a positive association was found (10,13,32,42,80,116,119,124,156), whereas in two populations, a positive association was found only in women (128) or young subjects (132). In 13 populations, no association was present (2,3,38,70,74,79,84,88,100,116,119,124,151). In three studies (116,119,124), both positive and negative associations are observed in different populations.…”
Section: Studies In Humansmentioning
confidence: 89%
“…The G3 T substitution in exon 10 was genotyped as described previously. 18 Genotyping of a C3 G polymorphism in exon 13 was determined by PCR amplification 19 (forward primer: 5Ј-AAC CCC TTC ACC ACA CTC AC-3Ј and reverse primer: 5Ј-CCA CAA AGA AGC TCC CAG AG-3Ј) followed by digestion with the restriction enzyme BanII.…”
Section: Genotypingmentioning
confidence: 99%
“…7 Also, a-adducin genotypes are associated with BP levels or the prevalence of hypertension in some but not all populations (Caucasian, African-American, Japanese). [8][9][10][11][12] Blood pressure response to diuretics has been reported to be more pronounced in participants with the Trp allele compared to those homozygous for the Gly allele. 5,7 To determine whether the a-adducin Gly460Trp polymorphism interacts with type of antihypertensive drug to modify risk of coronary heart disease (CHD) and other cardiovascular disease (CVD) outcomes, the Genetics of Hypertension-Associated Treatment (GenHAT) study examined genotype-treatment interaction in participants from the Antihypertensive and Lipid-Lowering treatment to prevent Heart Attack Trial (ALLHAT).…”
Section: Introductionmentioning
confidence: 99%